The Effect of Feeding Red Ginger (Zingiber officinale Rosc) as Phytobiotic on Broiler Slaughter Weight and Meat Quality - Herawati; Marjuki (International Journal of Poultry Science, 2011)
The research aimed to evaluate the potency of Red Ginger (Zingiber officinale Rosc) as a source of phytobiotic in the ration to increase physical quality of broiler meat. Two hundred of five days old broiler chickens were plotted into five different groups and each group was further divided into five sub-groups. Each group was given different rations, i.e.: R-0 (control ration without red ginger added); R-0.5, R-1.0, R-1.5, and R-2.0% (control ration added with red ginger at level 0.5, 1.0, 1.5, and 2.0% of the ration, respectively). All rations were designed as iso-protein ration with CP content of 21.0-23.0%, iso-caloric with energy content of 3150 kcal ME/kg, Ca 1.0%, and P 0.5%. The broilers were raised for 5 weeks. After five weeks all broilers were slaughtered and weighed to get data for carcass quality (slaughter weight, carcass weight, carcass percentage, fat weight and fat percentage) and the data of meat physical quality including pH, tenderness, water holding capacity (WHC), cooking loss (CL). The collected data were subjected to analysis of One Way Classification of Completely Randomized Design (CRD) and Duncan’s New Multiple Range Test (DMRT). The result showed that broilers given ration with red ginger showed significantly higher slaughter weight (P<0.05) and carcass percentage (P<0.01) but lower fat weight (P<0.05) than broilers given ration without red ginger. Feeding red ginger in the ration as treatment slightly increased pH and tenderness of broiler meat but decreased water holding capacity and cooking loss as compared to those in the control treatment without red ginger in the ration. Feeding of red ginger phytobiotic feed additive increased productive performance, carcass and meat quality of broiler. Feeding the phytobiotic feed additive at level 1.0 to 1.5% looked to be the most optimum level for those purposes. Further researches have to be conducted to evaluate the potential of red ginger as a source of phytobiotic feed additive to replace the chemical antibiotics.